2018
DOI: 10.4251/wjgo.v10.i9.244
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinogenesis: Insights into the cell death and signal transduction pathways: A review

Abstract: Colorectal carcinogenesis (CRC) imposes a major health burden in developing countries. It is the third major cause of cancer deaths. Despite several treatment strategies, novel drugs are warranted to reduce the severity of this disease. Adenomatous polyps in the colon are the major culprits in CRC and found in 45% of cancers, especially in patients 60 years of age. Inflammatory polyps are currently gaining attention in CRC, and a growing body of evidence denotes the role of inflammation in CRC. Several experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 157 publications
(149 reference statements)
1
29
0
Order By: Relevance
“…Activation of Smad3 is pivotal in the TGFβ/Smad pathway via the interaction of TGFβ and receptor. Phosphor-TGFβ receptor phosphorylates and initiates Smad2 and Smad3; therefore, the trimeric complex Smad2: Smad3: Smad4 establishes and triggered cell growth and survival (27). In the present study, we showed miR-145 reduced SMAD3 expression in vitro and in vivo, along with the decrease of Cdk4/Cyclin D1 and XIAP.…”
Section: Discussionsupporting
confidence: 59%
“…Activation of Smad3 is pivotal in the TGFβ/Smad pathway via the interaction of TGFβ and receptor. Phosphor-TGFβ receptor phosphorylates and initiates Smad2 and Smad3; therefore, the trimeric complex Smad2: Smad3: Smad4 establishes and triggered cell growth and survival (27). In the present study, we showed miR-145 reduced SMAD3 expression in vitro and in vivo, along with the decrease of Cdk4/Cyclin D1 and XIAP.…”
Section: Discussionsupporting
confidence: 59%
“…Dysregulation in apoptosis pathways may include alteration of genes responsible in apoptosis modulation such as KRAS and TP53 . It has been reported that about 30% of CRC cases were linked to KRAS oncogene mutations [ 94 ] and about 70% were linked to the p53 mutations [ 95 , 96 , 97 ], where involvement includes cell survival, proliferation, and dysregulation of apoptosis [ 94 , 98 , 99 , 100 ]. In a normal colonic epithelium, a high number of apoptotic cells may be found at the top of the colon crypt.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variation within genes encoding inflammatory mediators (6, 7) may have a modulatory role in colorectal carcinogenesis and affect the risk of developing CRC and survival. Due to different activated signaling cascades, the roles in later stages of cancer differ from those in early stages (3,15,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%